KESULITAN SISWA PADA PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) BERBASIS KURIKULUM MERDEKA DI KELAS IV SDN 09 SUNGAI KELAMBU TAHUN PELAJARAN 2023-2024 - Puput Handayani; Yusrain Yusrain; Hadisa Putri (CV. ADIBA AISHA AMIRA, 2024)
This research aims to find out and obtain information about the implementation process of the P5 program based on the independent curriculum in Class IV SDN 09 Sungai Kelambu for the 2023-2024 academic year, to find out the internal difficulty factors of students in the P5 based on the independent curriculum in Class IV SDN 09 Sungai Kelambu for the 2023 academic year. -2024 and external difficulty factors for students in P5 based on the independent curriculum in Class IV SDN 09 Sungai Kelambu for the 2023-2024 academic year. This research uses a qualitative approach with a phenomenological type of research. The results of the research concluded that during the implementation process of the P5 program based on the independent curriculum in Class IV of SDN 09 Sungai Kelambu for the 2023-2024 academic year, during the process of implementing the P5 program, the principal and teachers agreed on the theme that would be applied to class IV students by choosing two themes, namely the theme of entrepreneurship and local wisdom theme. As for the entrepreneurship theme, there is a project program, namely saving, while the local wisdom theme is farming, including planting chili plants. Apart from that, there are internal difficulties for students in P5 based on the independent curriculum in Class IV SDN 09 Sungai Kelambu for the 2023-2024 academic year, there are several skills as follows: first, students' ability to understand the material. Second, students' emotions and attitudes towards learning. Meanwhile, the external difficulties of students in P5 based on the independent curriculum in Class IV SDN 09 Sungai Kelambu 2023-2024 Academic Year First, family disharmony, second, the condition of the living environment, and third is the school environment